An Urgent Need for Inclusion of GIS in the Curriculum of Geography and Computer Science - Mali, Prasanta (SCHOOL SCIENCE, 2013)
In our country some of the latest developments in technologies in many of the educational fields are not incorporated at the right time. Sometimes they are not recognised as simple initial stages. But, if seen deeply, it will be revealed that they are very fundamental in the context of growing computer education and their applications. In the present day situation, many subject areas at the stages of elementary education lack proper emphasis on important applications desired. These applications will not only make that subject more interesting to the students but also attract many talents in that area. We would see that same contents are actually being taught in different stages at the school level in the present curriculum. Perhaps the one being suggested here exists but not in a form desired in the present day situation. The application of GIS – Geographical Information System technologies in the curriculum of Geography at the school level. Though it may initially sound to be something from a higher platform, but with the changing character of education this would emerge as an indispensable area for the subject. Its inclusion would not only change the character of the entire subject of Geography as a science of the Earth, but also help the country to collect the maximum data needed for the micro level planning for the country planners. It is still seemingly obscure but through this dissertation we would like to emphasise that it is inevitable in the present day situation. Inclusion of GIS in the curriculum will make the study of geography very exciting and useful. More importantly the data acquisition will become very easy. There will be mass involvement of the education system in data collection process. Enormous quantities of accurate data will flow from various institutions with the latest updations. Both the objectives of data collection and organisation will met without extra effort in collecting data.